1992
DOI: 10.1111/j.1651-2227.1992.tb12343.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac rhabdomyomas in neonates: report of three cases

Abstract: Three cases of intracardiac rhabdomyomas in neonates are presented. All were diagnosed by ultrasound, one prenatally and two directly after birth. Two of the patients were operated on during the neonatal period. The operations were carried out on the ultrasound findings alone. One patient was considered inoperable and died at three weeks of age. The two surviving patients have no cardiac symptoms and involution of the tumors has taken place. Two of the three patients have shown signs of tuberous sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Prenatally, they are usually diagnosed during the second or third trimester6, 10, 15–18. Cardiac complications are rare and mainly involve fetal dysrythmia12, 19–23, but other complications such as intracardiac obstruction and cardiac failure may be associated. In their recent review, Chao et al 24 showed that these complications were strong predictors of negative neonatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatally, they are usually diagnosed during the second or third trimester6, 10, 15–18. Cardiac complications are rare and mainly involve fetal dysrythmia12, 19–23, but other complications such as intracardiac obstruction and cardiac failure may be associated. In their recent review, Chao et al 24 showed that these complications were strong predictors of negative neonatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The prenatal diagnosis is often made after the 20th week of gestational age. Tumors may be incidentally found during routine obstetrical ultrasonography or evaluation for fetal cardiac arrhythmia [145,[148][149][150]. Hydrops fetalis, intrauterine death, or sudden death immediately after birth may rarely occur [151][152][153][154].…”
Section: Cardiac Rhabdomyomamentioning
confidence: 99%
“…On ultrasonic examination, rhabdomyoma generally exhibits a uniform high echo, a myocardial echo which is stronger than normal and tuberous sclerosis may also be present. The identification of multiple tumors is common, and such tumors may cause significant hemodynamic disturbances as a result of outflow obstruction or arrhythmias (7). The occurrence of cardiac tumors may cause numerous types of serious blood disorder in fetuses and neonates and may cause fetal mortality.…”
Section: Introductionmentioning
confidence: 99%